Illicit trafficking a reference handbook - Kelly Robert J; Maghan Jess; Serio Joseph D (California ABC-CLIO, 2005)
Highlights: - Written in language accessible to students- Offers an easy-to-grasp overview of this growing modern problem- Defines key terms and concepts
Keywords: Drug traffic; Illegal arms transfers; Money laundering; Smuggling; Transnational crime